Anti-Inflammatory and Protective Effects of Juncus effusus L. Water Extract on Oral Keratinocytes. (4th January 2022) - Wada, Akihiro; Murakami, Keiji; Ishikawa, Yumi; Amoh, Takashi; Hirao, Kouji; Hosokawa, Yuki; Hinode, Daisuke; Miyake, Yoichiro; Yumoto, Hiromichi
Abstract : Periodontitis is a chronic inflammatory disease caused by periodontopathogenic bacteria that form biofilms in periodontal pockets. The gingival epithelium acts as the first physical barrier in fighting attacks by periodontopathogenic pathogens, such as the primary etiological agent Porphyromonas gingivalis, and various exogenous chemicals, as well as regulates the local innate immune responses. Therefore, the development of novel oral care products to inhibit inflammatory reactions caused by bacterial infection and protect the gingival epithelium is necessary. Juncus effusus L. has generally been used as an indigenous medicine, such as a diuretic, an antipyretic, and an analgesic, in ancient practice. In this study, we examined the effects of a water extract from J. effusus L. on the inhibition of the inflammatory reaction elicited by bacterial infection and protection of the oral epithelium by chemical irritation. Pretreatment of oral epithelial cells with the water extract from J. effusus L. significantly reduced P. gingivalis or its lipopolysaccharide- (LPS-) mediated production of chemokines (interleukin-8 and C-C-chemokine ligand20) in a concentration-dependent manner with comparable to or greater effects than epigallocatechin gallate and protected oral epithelial cells from injury by chemical irritants, cetylpyridinium chloride, and benzethonium chloride. Moreover, the water extract from J . effusus L. in the presence of antimicrobial agents or antifibrinolytics already used as ingredients in mouthwash could significantly reduce the production of chemokines from P. gingivalis LPS-stimulated oral epithelial cells in a concentration-dependent manner. These findings suggest that the water extract from J . effusus L. is potentially useful for oral care to prevent oral infections, such as periodontal infections, and maintain oral epithelial function.